The role of immune cells in the pathogenesis of connective tissue diseases-associated pulmonary arterial hypertension - Li, Zhe; Ma, Juan; Wang, Xuejing; Zhu, Liquan; Gan, Yu; Dai, Baoquan (Frontiers in Immunology, 2024)
Connective tissue diseases-related pulmonary arterial hypertension (CTD-PAH) is a disease characterized by an elevated pulmonary artery pressure that arises as a complication of connective tissue diseases. The number of patients with CTD-PAH accounts for 25.3% of all PAH patients. The main pathological features of CTD-PAH are thickening of intima, media and adventitia of pulmonary arterioles, increased pulmonary vascular resistance, autoimmune activation and inflammatory reaction. It is worth noting that abnormal immune activation will produce autoantibodies and release cytokines, and abnormal immune cell recruitment will promote inflammatory environment and vascular remodeling. Therefore, almost all forms of connective tissue diseases are related to PAH. In addition to general therapy and targeted drug therapy for PAH, high-dose glucocorticoid combined with immunosuppressant can quickly alleviate and stabilize the basic CTD-PAH disease. Given this, the development of therapeutic approaches targeting immune dysregulation and heightened inflammation is recognized as a promising strategy to prevent or reverse the progression of CTD-PAH. This review explores the potential mechanisms by which immune cells contribute to the development of CTD-PAH and examines the clinical application of immunosuppressive therapies in managing CTD-PAH.